Knowledge, attitudes and practice of secondary school girls towards contraception in Limpopo Province - Dorah U. Ramathuba; Lunic B. Khoza; Mutshinyalo L. Netshikweta (AOSIS, 2012)
Unplanned teenage pregnancy constitutes an important health problem, whilst contraceptive services are free throughout South Africa and the number of Termination of Pregnancy (TOP) services is increasing. The purpose of this study was to assess the knowledge, attitudes and practices of secondary school girls towards contraception in Thulamela Municipality of Limpopo Province, South Africa. A quantitative descriptive study design was used and respondents were selected by convenience sampling from a population of secondary school girls, the sample consisting of 273 girls in Grades 10-12. A self-administered questionnaire was used to collect data and analysed by computing frequencies and percentages using the Statistical Package for Social Sciences. Findings showed that respondents were aware of different contraceptive methods that can prevent pregnancy. However, most did not have knowledge of the emergency contraceptive, intra-uterine device and female condom. Pressure from male partners, fear of parental reaction to the use of contraceptives, reluctance to use contraceptives, poor contraceptive education and lack of counselling were seen as the main causes of ineffective contraceptive use and non-utilisation. Possible modalities of intervention deal with providing contraceptive counselling and care to empower these school girls to make informed choices on reproductive health.